Effect of abiotic stress factors on growth and secondary plant metabolism in withania somnifera (L) dunal - Lini Jacob (Department of Plant Physiology, College of Agriculture, 2006)
An experiment was conducted in the Department of Plant Physiology, College of Agriculture, Vellayani, to study the effect of abiotic stress factors on growth and secondary plant metabolism in Withania somnifera (L.) Dunal. The study analyzed the effect of abiotic stresses on growth, physiological, biochemical parameters and also withanolide content-the secondary metabolite of this medicinal plant. The abiotic stresses were three levels of light stress at 25%, 50% and 75% shade and three levels of water stress at 25%, 50%, and 75%FC along with control under optimum conditions. The treatments were imposed for a period of 30 days on 5 month old plants. Growth parameters such as plant height, Dry matter production, length of tap root and physiological parameters such as specific leaf area and relative water content were recorded highest in 75% shaded plants. Stomatal conductance was higher in 25% shade condition. Stomatal frequency and stomatal index were higher in control plants. The total chlorophyll, chlorophyll a and chlorophyll b increased under different field capacity levels and recorded the highest value under 25%FC. Stable isotopes discrimination studies showed significant variation among the treatments. 50% shade showed highest value in stable isotopes. Biochemical parameters total soluble protein, starch content, total phenols, ascorbic acid, free amino acids and reducing sugars were recorded from the leaves of the stress imposed plants. The total soluble protein and ascorbic acid were highest in control condition whereas starch recorded maximum under 25 per cent shade condition. Reducing sugar and phenol content showed highest under 75 per cent shade condition. Amino acid was highest under 25 per cent of field capacity. The secondary metabolite were recorded from the stress imposed, sun dried roots of the plants. The secondary metabolite withanolide was estimated spectophotometrically. The withanolide content was high in 75% shade (0.64%) condition after imposing the stress for a period of 30 days. The activity of free radical scavenging enzymes namely peroxidase and polyphenol oxidase were also estimated in the above treatments and was found to be highly active in 75% field capacity level. The water stress at different field capacity levels reduced the growth of the plants while the activities of free radical scavenging enzymes were shown an increase among the treatments. There was a positive relation with the antioxidant enzymes under 75% FC and withanolide content which was reported to have an antioxidant activity. The gene sequence analysis revealed that hmgr in Withania somnifera is having a size of 262 base pairs. Similarity search using BLAST showed that high percent similarity exist in hmgr across many crop plants and important medicinal plants. Expression levels of HMG Reductase were assessed by relative quantitative RT-PCR and there was a maximum expression of hmgr under 75% shade condition followed by 25% shade. The present investigation has shown that exposure to abiotic stress factors invariably leads to better accumulation of secondary metabolites. The differential expression of hmgr can be a crucial factor in deciding the levels of biosynthesis of secondary metabolites in Withania somnifera when exposed to abiotic stress situation. An understanding of this role of abiotic stress factors is of great importance in phytomedicinal enrichment programme.